# 36-x=(13x-5)+(36-x)

## Simple and best practice solution for 36-x=(13x-5)+(36-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 36-x=(13x-5)+(36-x) equation:

36-x=(13x-5)+(36-x)
We move all terms to the left:
36-x-((13x-5)+(36-x))=0
We add all the numbers together, and all the variables
-x-((13x-5)+(-1x+36))+36=0
We add all the numbers together, and all the variables
-1x-((13x-5)+(-1x+36))+36=0

We calculate terms in parentheses: -((13x-5)+(-1x+36)), so:
(13x-5)+(-1x+36)
We get rid of parentheses
13x-1x-5+36
We add all the numbers together, and all the variables
12x+31
Back to the equation:
-(12x+31)

We get rid of parentheses
-1x-12x-31+36=0
We add all the numbers together, and all the variables
-13x+5=0
We move all terms containing x to the left, all other terms to the right
-13x=-5
x=-5/-13
x=5/13

`